2023
DOI: 10.3390/vetsci10020169
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Effect of Ivermectin on the Bacterial Microbiota from Fecal Samples in Chinchillas (Chinchilla lanigera)

Abstract: The gastrointestinal microbiota plays an important role in health of the host animals and the detrimental influence of pharmaceutical treatment on the fecal microbiota receives an increasing concern. The clinical use of ivermectin on chinchillas has not yet been evaluated. The purpose of our study was to assess the influence of ivermectin injection on the fecal bacterial microbiota of chinchillas. A with-in subject, before and after study was performed on 10 clinically healthy chinchillas during a 14-day perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…While it is commonly accepted that the gut microbiota in cattle plays an important part in determining the chemical makeup of the dung (Hammer et al, 2016), the chemical analyses of cattle dung in our study under both treatments have found that no significant change in the volatile composition takes place, even after analysing the possible changes across time (7 and 14 days post‐administration), which leads us to propose that no major alteration of the microbiota in the digestive tract of cattle occurs as a direct effect of the application of IVM. For example, in a study carried out with chinchillas, the use of IVM, in the short term, did not alter the richness and diversity of the main faecal microbiota present in domestic herbivores (Firmicutes, Bacteroidetes, Verrucomicrobia, Spirochaetes and Proteobacteria) (Ma et al, 2023). These results could explain that IVM does not have a direct short‐term effect on the composition of the intestinal microbiota; however, excessive and prolonged use of IVM could lead to an imbalance in the intestinal microbiome (bacterial intestinal dysbiosis) (Andrade‐Belo et al, 2023) although the effect in terms of volatile composition is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is commonly accepted that the gut microbiota in cattle plays an important part in determining the chemical makeup of the dung (Hammer et al, 2016), the chemical analyses of cattle dung in our study under both treatments have found that no significant change in the volatile composition takes place, even after analysing the possible changes across time (7 and 14 days post‐administration), which leads us to propose that no major alteration of the microbiota in the digestive tract of cattle occurs as a direct effect of the application of IVM. For example, in a study carried out with chinchillas, the use of IVM, in the short term, did not alter the richness and diversity of the main faecal microbiota present in domestic herbivores (Firmicutes, Bacteroidetes, Verrucomicrobia, Spirochaetes and Proteobacteria) (Ma et al, 2023). These results could explain that IVM does not have a direct short‐term effect on the composition of the intestinal microbiota; however, excessive and prolonged use of IVM could lead to an imbalance in the intestinal microbiome (bacterial intestinal dysbiosis) (Andrade‐Belo et al, 2023) although the effect in terms of volatile composition is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some suggest that the IVM metabolites themselves could cause a greater attraction or that a change—caused by IVM—in the gut microbiota capable of modifying the volatiles of the excrement could attract more beetles (Lumaret et al, 1993; Wardhaugh & Mahon, 1991), or that the composition of amino acids present in the excrement after treatment could cause a change in attraction (Bernal et al, 1994). The few studies carried out to date on the possible direct effects of IVM on the intestinal bacterial microbiota do not show significant changes in abundance and diversity, at least in the short term (Ma et al, 2023). Following a similar trend with soil microorganisms, the study by Mougin et al (2003) also showed that IVM did not seem to significantly affect this fauna after detecting the drug in this matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the study showed that the Firmicutes and Bacteroidetes phyla were the dominant microbiota in the chinchilla [ 6 ]. Our team evaluated the effect of ivermectin treatment on the fecal bacterial microbiota of healthy chinchillas [ 7 ]. In addition to the effect of gastrointestinal drugs on the fecal microbiota, differences in microbial composition between compartments of the chinchilla gastrointestinal tract are also of clinical interest.…”
Section: Introductionmentioning
confidence: 99%